Protection of a Wife’s Dignity Under Article 4, Section 2 of Law No. 1 of 1974 from the Perspective of Maqāṣid Al-Syari’ah - Farendra Budi Saputra (Eduvest - Journal of Universal Studies, 2026)
This research examines the effectiveness of Article 4 paragraph (2) of Law Number 1 of 1974 concerning Marriage in protecting the dignity of wives in the practice of polygamy permits in religious courts. The focus of the research is the use of the reason for the wife's inability to serve her husband as the basis for the judge's consideration. The method used was qualitative with a sociological juridical approach through a literature study of regulations, court decisions, and related literature. The results of the study show that normatively the article is limitative and aims to limit polygamy, but in practice the judge tends to rely on the wife's confession without objective evidence. This has the potential to be influenced by power relations and psychological pressure, thereby weakening the protection of the wife's dignity. In the perspective of maqāṣid al-shari'ah, these reasons do not meet the urgent need to maintain the five main objectives of the shari'a. Therefore, the effectiveness of this article is considered low and it is necessary to tighten the conditions for polygamy to ensure justice and protection of women.